Respuesta :
Answer:
D.
Step-by-step explanation:
h(x)=f(x)g(x) means multiply the expression for f to the expression for g.
That is the problem is just asking you to do (11x-5)(-2x-4).
Let's use foil.
First: 11x(-2x)=-22x^2
Outer: 11x(-4)=-44x
Inner: -5(-2x)=10x
Last: -5(-4)=20
------------------------Add together!
-22x^2-34x+20
D.
h(x) = [tex]-22x^{2} -34x+20[/tex]
Option D is correct.
What is an equation?
An equation is a mathematical statement that is made up of two expressions connected by an equal sign.
Given equations
f(x) = 11x - 5
g(x) = - 2x - 4
h(x) = f(x) g(x)
h(x) = [tex](11x -5) \times (-2x-4)[/tex]
h(x) = [tex]11x \times (-2x) +11x \times (-4) -5 \times (-2x) -5 \times (-4)[/tex]
h(x) = [tex]-22x^{2} -44x+10x+20[/tex]
h(x) = [tex]-22x^{2} -34x+20[/tex]
Option D is correct.
Find out more information about equation here
brainly.com/question/2263981
#SPJ2